Remote and Hybrid Work Models: Enhancing Employee Engagement and Redefining Performance Management in a New Era - Tawalbeh, Jawad (Journal of Posthumanism, 2025)
The rise of remote and hybrid work models has redefined traditional workflows, employee interactions, and management practices. This paper examines the challenges and opportunities these models present in enhancing employee engagement and reshaping performance management frameworks. By incorporating Partial Least Squares (PLS) analysis, the study identifies critical factors driving engagement and performance, offering actionable insights for building resilient and future-ready workplaces. The findings reveal that communication quality, technological infrastructure, and leadership approach serve as significant predictors of employee engagement in distributed work environments, while outcome-focused performance metrics demonstrate stronger correlation with productivity than traditional time-based measures. This research provides a strategic framework for organizations navigating the complexities of remote and hybrid work arrangements in the post-pandemic era.